2013
DOI: 10.1016/j.neuroscience.2013.03.002
|View full text |Cite
|
Sign up to set email alerts
|

PACAP deficiency sensitizes nigrostriatal dopaminergic neurons to paraquat-induced damage and modulates central and peripheral inflammatory activation in mice

Abstract: Exposure to the pesticide paraquat (PQ) increases the risk of Parkinson’s disease (PD), and its effect may be modulated by genetic or other environmental factors. The neuropeptide PACAP (pituitary adenylyl cyclase activating polypeptide, Adcyap1) has been shown to enhance tyrosine hydroxylase (TH) and VMAT2 expression, protect dopaminergic (DA) neurons against the neurotoxin 6-hydroxydopamine, regulate neuronal mitochondria, and inhibit inflammation. Decreased expression of PACAP may thus interact with environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…Accumulating evidences support the view that PACAP is neuroprotective on dopaminergic neurons as shown in cell culture experiments [124,125] and in vivo PD models using the neurotoxins, 6-OHDA and MPTP [126]. Dopaminergic neurons in PACAP-deficient mice are also more susceptible to the toxin paraquat and show changes in microglia and immune responses [127].…”
Section: Pituitary Adenylate Cyclase-activating Polypeptide (Pacap)mentioning
confidence: 87%
“…Accumulating evidences support the view that PACAP is neuroprotective on dopaminergic neurons as shown in cell culture experiments [124,125] and in vivo PD models using the neurotoxins, 6-OHDA and MPTP [126]. Dopaminergic neurons in PACAP-deficient mice are also more susceptible to the toxin paraquat and show changes in microglia and immune responses [127].…”
Section: Pituitary Adenylate Cyclase-activating Polypeptide (Pacap)mentioning
confidence: 87%
“…A review of quantitative inflammatory effects was not provided in 7 of 8 previously mentioned unblinded studies that reported more activated microglia activation in PQ treated mice (S3 Appendix). One blinded study [54] that used a statistical bootstrapping procedure found significantly more 7–8 μm diameter (activated) microglia and fewer 3 μm diameter microglia in PQ-treated mice compared to controls. Interestingly, in this study, PQ had no effect on the mean number of TH + neurons in the SNpc.…”
Section: Discussionmentioning
confidence: 99%
“…PACAP was shown to mitigate 6-OHDA and MPTP-induced loss of dopaminergic neurons in animal models of PD [17,71,72,89]. Furthermore, PACAP deficiency sensitizes dopaminergic neurons to paraquat-induced neuroinflammation in vivo [92]. Some studies support the view that PACAP27 is a more potent neuropeptide than PACAP38 and VIP (vasoactive intestinal peptide) in, for example, voltage clamped preparations of rat jejunum [15].…”
Section: Introductionmentioning
confidence: 99%